AI-based Machine Translations in Tourism and Hospitality: An Exploratory Study of Travelers’ Perceptions and Future Challenges - Elisa Rancati; Irakli Abashidze; Alessandro d‘Agata (European Scientific Journal, ESJ, 2025)
With the progress of AI-driven technologies, machine translation has significantly impacted tourists' travel experiences by transforming how they engage with or interpret language at their destinations. However, the body of empirical literature on the benefits, obstacles, and future prospects of these emerging technologies in tourism and hospitality is yet to be fully explored. This study aims to explore and outline 320 travelers' perceptions of machine translation. A distinctive sample of Italian travelers, along with their current and potential customers in the digital environment, is analyzed. Descriptive statistics was used to present the number and main characteristics of travelers‘ perceptions about AI-based machine translators. Travelers were grouped into two clusters based on perceived benefits and implementation challenges. Our findings contribute to the growing literature on AI-based machine translators and offer practical insights by mapping the benefits, challenges, outlook, and maturity levels of machine translations. The results provide both theoretical and practical insights for improving the use of AI-based machine translations and their role in tourism and hospitality industries. This is among the first studies exploring the tourism and hospitality approaches adopted by travelers to manage their interactions with AI-based machine translations while traveling abroad.